2019
DOI: 10.1007/s00265-018-2601-8
|View full text |Cite
|
Sign up to set email alerts
|

A framework for studying social complexity

Abstract: Social complexity has been one of the recent emerging topics in the study of animal and human societies, but the concept remains both poorly defined and understood. In this paper, I critically review definitions and studies of social complexity in invertebrate and vertebrate societies, arguing that the concept is being used inconsistently in studies of vertebrate sociality. Group size and cohesion define one cornerstone of social complexity, but the nature and patterning of social interactions contribute more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
257
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(263 citation statements)
references
References 170 publications
6
257
0
Order By: Relevance
“…Although primary unit predominantly splits species into three distinct clusters, in line with previous studies (Kappeler, 2018), we found some evidence that the partitioning may require revisiting. Based on our findings, the primary unit appears to be a key dimension for categorizing societies, underlying most of the variation across species.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although primary unit predominantly splits species into three distinct clusters, in line with previous studies (Kappeler, 2018), we found some evidence that the partitioning may require revisiting. Based on our findings, the primary unit appears to be a key dimension for categorizing societies, underlying most of the variation across species.…”
Section: Discussionsupporting
confidence: 90%
“…The way the variables are clustered shows connections between them. When looking at the contributions of the different variables to the principal components, the first three components accounted for 67.74% of the variance ( Figure A1 This partition into three clusters reflects Kappeler's description of forms of social organization for animals (Kappeler, 2018): live solitarily, coordinate with a partner (as a pair), or with a group. A large number of species in the first cluster with individuals as the primary unit suggest that there is a fourth option to this theory: a social lifestyle without coordinating all activities as a fixed group.…”
Section: Re Sultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Thus, although group size is a descriptive measure, it has a causal motivation. The availability of group size data across a wide range of species enabled early comparative analyses [10,9], but mainly focused on vertebrate social complexity rather than other groups like social insects [5]. The biological relevance of interspecific comparisons, and in particular the use of group size as a measure of complexity, has been strongly debated [12][13][14].…”
Section: Group Sizementioning
confidence: 99%